Aluminum alloy wire

JP7639468B2Active Publication Date: 2025-03-05PROTERIAL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021055355
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-03-05
Estimated Expiration
2041-03-29

AI Technical Summary

Benefits of technology

【0010】 本願において開示される一実施の形態によれば、アルミニウム合金線材の再結晶を抑制して、耐熱性を向上できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639468000001
    Figure 0007639468000001
Patent Text Reader

Abstract

To improve heat resistance by suppressing recrystallization of an aluminum alloy wire material.SOLUTION: A wire made of an aluminum alloy, the aluminum alloy containing 0.2 to 1.0 mass% of Zr and 0.1 to 1.0 mass% of Co, with the balance being aluminum and inevitable impurities, a tensile strength at room temperature is 170 MPa or more, an elongation of 10% or more, and a stress is 40 MPa or more when tensile deformation is performed at a strain rate of 10-5 / sec at a temperature of 250°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy wire. [Background technology]

[0002] Aluminum alloys for conductors tend to have the minimum amount of alloying elements added to increase electrical conductivity. For this reason, in addition to alloying, work hardening by introducing processing strain is generally used to improve material strength. One issue with introducing processing strain is the reduction in ductility at room temperature. When aluminum alloys reach high temperatures, the reduction in strength due to recrystallization and creep deformation become significant, making it difficult to prevent stress relaxation at the connection terminals. This stress relaxation can cause an increase in the electrical resistance of aluminum alloy wires.

[0003] In order to improve the ductility of an aluminum alloy wire at room temperature, it is considered to add Zr to the aluminum alloy.

[0004] Patent Document 1 describes that an Al-Zr-Fe-Si based aluminum alloy material is cast, processed, and then subjected to an aging heat treatment. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 57-39164 Summary of the Invention [Problem to be solved by the invention]

[0006] Zr, a strengthening element, is likely to diffuse through grain boundaries during aging heat treatment and form coarse grain boundary precipitation phases. However, even if the strength of conductors made of pure aluminum or solid-solution strengthened aluminum alloys that do not contain Zr is increased by processing strengthening, the strength decreases due to recrystallization at temperatures above 120°C, and creep deformation occurs, resulting in a problem that heat resistance cannot be maintained.

[0007] An object of the present invention is to suppress recrystallization of an aluminum alloy wire rod and improve the heat resistance. [Means for solving the problem]

[0008] A brief outline of a representative embodiment of the present invention will be described below.

[0009] The aluminum alloy wire rod of one embodiment is a wire rod made of an aluminum alloy, the aluminum alloy containing 0.2 to 1.0 mass % Zr, 0.1 to 1.0 mass % Co, and the balance being aluminum and unavoidable impurities, and has a tensile strength of 170 MPa or more at room temperature, an elongation of 10% or more, and a strain rate of 10 at a temperature condition of 250°C. -5 The stress when tensile deformed at 1000 / sec is 40 MPa or more. Effect of the Invention

[0010] According to one embodiment disclosed in the present application, recrystallization of an aluminum alloy wire can be suppressed, and heat resistance can be improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The embodiment will be described in detail below.

[0012] In order to solve the above-mentioned problems, the present inventors have studied the changes in various properties when the types of alloying elements and manufacturing conditions are appropriately changed. As a result, they have found that it is good to use Co or Ni and Zr as alloying elements. They have also found that by specifying the strain rate of the aluminum alloy wire and evaluating the tensile strength at high temperatures, it is possible to suppress recrystallization of the aluminum alloy wire and improve the heat resistance. The present invention has been made based on this knowledge.

[0013] (Embodiment) Hereinafter, an embodiment of the present invention will be described. In this specification, a numerical range expressed using "to" means a range including the numerical values ​​before and after "to" as the lower and upper limits.

[0014] <Aluminum alloy wire> Hereinafter, an aluminum alloy wire according to an embodiment of the present invention will be described taking as an example a case in which Co and Zr are mainly used as alloying elements.

[0015] <Chemical composition> First, the chemical composition of the aluminum alloy (hereinafter also simply referred to as alloy) constituting the aluminum alloy wire (hereinafter also simply referred to as alloy wire) will be described.

[0016] The chemical composition of the alloy is Co: 0.1~1.0 mass%, Zr: 0.2~1.0 mass%, Fe: 0.02~0.15 mass%, Si: 0.02~0.15 mass%, Mg: 0~0.2 mass%, Ti: 0~0.10 mass%, B: 0~0.03 mass%, Cu: 0~1.0. 0% by mass, Ag: 0-0.50% by mass, Au: 0-0.50% by mass, Mn: 0-1.00% by mass, Cr: 0-1.00% by mass, Hf: 0-0.50% by mass, V: 0-0.50% by mass, Sc: 0-0.50% by mass, and the remainder: Al and inevitable impurities.

[0017] As described later, most of Co reacts with Al to form crystals (Al-Co compounds) during the manufacturing process (casting) of the alloy wire, and exists as a compound phase in the finally obtained alloy wire. The Al-Co compounds actually exist in the form of Al-Co-Fe compounds that absorb Fe, which is inevitably present in the aluminum alloy. The Al-Co-Fe compounds contribute to the refinement of Al recrystallized grains in the alloy and improve the elongation of the alloy wire. Although Co may reduce the electrical conductivity of the alloy, by setting the Co content to 0.1 mass% to 1.0 mass%, it is possible to obtain the effect of suppressing the decrease in electrical conductivity due to Co in the alloy wire while having a high level of strength, elongation, and heat resistance due to Co in a well-balanced manner. The Co content is preferably 0.2 mass% to 1.0 mass%, and more preferably 0.3 mass% to 0.8 mass%.

[0018] Here, the addition of Co in the above ratio will be described, but as will be described later, even if the same amount of Ni or Fe is added instead of Co, the same effect as when Co is added in the above ratio can be obtained.

[0019] As described later, Zr exists mainly in a solid solution state in the ingot (cast material) after casting, but precipitates as an Al-Zr compound in the alloy wire after aging heat treatment. The Al-Zr compound mainly contributes to improving the heat resistance of the alloy wire. If the content of Zr is excessively high, it may reduce the ductility of the alloy during the manufacturing process of the alloy wire, preventing the alloy wire from being thinned. In this regard, by setting the content of Zr to 0.2 mass% to 1.0 mass%, the ductility of the alloy can be kept high and the desired heat resistance can be obtained in the alloy wire. The content of Zr is more preferably 0.3 mass% to 0.6 mass%.

[0020] Fe is an ingredient derived from the aluminum raw material and inevitably taken in. Fe contributes to improving the strength of the alloy. When Fe is crystallized as FeAl3 during casting or precipitated as FeAl3 during aging heat treatment, it may reduce the ductility of the alloy and hinder the thinning of the alloy wire during manufacturing. In this embodiment, by blending Co, when the Al-Co compound is crystallized, Fe is absorbed to form an Al-Co-Fe compound. As a result, by making Fe into an Al-Co-Fe compound, the formation of FeAl3 is suppressed. As a result, the strength of the alloy can be improved while suppressing the decrease in the ductility of the alloy. From the viewpoint of absorption by the Al-Co compound, the content of Fe is preferably equal to or less than the content of Co, and is set to 0.02 mass% to 0.15 mass%. This allows the alloy wire to be thinned while obtaining high strength. The content of Fe is preferably 0.04 mass% to 0.15 mass%. Fe may be added so as to obtain a predetermined content.

[0021] Like Fe, Si is an element that is inevitably incorporated from the aluminum raw material. Si contributes to improving the strength of the alloy by dissolving in the Al crystal grains of the alloy or precipitating together with Fe. Like Fe, Si may reduce the elongation of the alloy and hinder the thinning of the alloy wire. However, by setting the Si content to 0.02 mass% to 0.15 mass%, it is possible to improve the strength while suppressing the reduction in the elongation of the alloy. The Si content is preferably 0.04 mass% to 0.12 mass%. Note that Si may be added to achieve a predetermined content.

[0022] In the alloy of this embodiment, Ti replaces a part of Zr atoms in the Al-Zr compound formed in the alloy wire after aging heat treatment, and precipitates as an Al-Zr-Ti compound. The Al-Zr-Ti compound has the same crystal structure as the Al-Zr compound, and mainly contributes to improving the heat resistance of the alloy wire. Similarly to Zr, if the content of Ti is excessively high, it may reduce the ductility of the alloy during the manufacturing process of the alloy wire, preventing the alloy wire from being thinned. In this regard, by setting the content of Ti to 0 mass% to 0.1 mass%, the ductility of the alloy can be maintained high and the desired heat resistance can be obtained in the alloy wire.

[0023] Mg, B, Cu, Ag, Au, Mn, Cr, Hf, V and Sc are optional components that are derived from the aluminum raw material and are incorporated or added as necessary. Here, optional components refer to components that may or may not be contained. Each alloying element suppresses the coarsening of the crystal grains of the Al phase in the alloy wire rod, and contributes to improving its strength. Among these, Cu, Ag and Au can precipitate at the grain boundaries and improve the grain boundary strength. By setting the content of each alloying element within the above range, the decrease in the elongation of the alloy is suppressed and the effects of each alloying element can be obtained.

[0024] The remainder other than the above-mentioned components is Al and inevitable impurities. Here, inevitable impurities refer to those that are inevitably introduced during the manufacturing process of the alloy wire and are present in such a small amount that they do not affect the properties of the alloy wire. Examples of inevitable impurities include Ga, Zn, Bi, and Pb.

[0025] From the viewpoint of electrical conductivity of the alloy wire, the Al content is preferably 97 mass % or more, more preferably 98 mass % or more, and further preferably 98.4 mass % or more.

[0026] <Metal structure> Next, the metal structure of the aluminum alloy will be described.

[0027] The aluminum alloy wire rod of the present embodiment has a metal structure including Al crystal grains, Al-Co-Fe compounds, and Al-Zr compounds. In the metal structure, the Al-Co-Fe compounds and the Al-Zr compounds are dispersed at the grain boundaries.

[0028] The Al-Co-Fe compound is a crystallized phase formed when the molten metal is cooled and solidified during casting of the aluminum alloy, or when the high-temperature cast material is cooled to around room temperature after solidification. In other words, the Al-Co-Fe compound is a crystallized substance formed in the aluminum alloy at the stage of the cast material.

[0029] The Al-Zr compound is a precipitate phase formed by the aging heat treatment, in which the cast material cooled to room temperature is heated and held in a high-temperature atmosphere below the melting point. Specifically, the precipitate is formed only when the metal elements that were dissolved in the Al phase of the cast material diffuse and coagulate in the Al phase by the aging heat treatment. In other words, the precipitate does not exist in the Al alloy at the stage of the cast material, but exists in the alloy wire after the aging heat treatment.

[0030] The size of the Al-Zr compound is distributed in the range of 1 nm to several hundreds of nm, but it is preferable that the ratio of fine precipitates having a size of 1 nm to 100 nm is greater than the ratio of precipitates not included in the size range of 1 nm to 100 nm. By reducing the size of the precipitates made of Al-Zr compounds to 1 nm to 100 nm, the number of precipitates can be increased even when the content of alloy elements is reduced, and the effect of the precipitates can be obtained in a well-balanced manner. In addition, since the ductility of the alloy can be maintained at a high level, the degree of processing can be increased in the wire drawing process, and the diameter of the alloy wire can be made thinner.

[0031] The size of the Al-Co-Fe compound is preferably 20 nm or more and 1 μm (1000 nm) or less. The Al-Co-Fe compound can be made large by, for example, ensuring a sufficient aging time. If the compound is too small, the ductility of the alloy wire may decrease. In this regard, the size of the compound is 20 nm or more, so that the ductility can be increased. On the other hand, if the compound is too large, recrystallization is likely to occur at the aging heat treatment stage, and the grain size may become coarse, which may decrease the strength of the alloy wire. From the viewpoint of obtaining high strength, the size of the compound is preferably 1 μm or less. Note that Co atoms diffuse faster in the Al structure than Zr atoms, so the size of the Al-Co-Fe compound is larger than that of the Al-Zr compound. As described later, the role of the Al-Co-Fe compound is to suppress the growth of recrystallized grains in the early stage of the aging heat treatment. For this reason, the Al-Co-Fe compound may be larger than the Al-Zr compound in the metal structure after the aging heat treatment is completed.

[0032] The shape of the compound is not particularly limited, but the Al-Co-Fe compound is preferably spherical or spheroidal. The Al-Zr compound is preferably spherical, but may be of an irregular shape. The spheroidal shape refers to a shape that is circular in the direction perpendicular to the longitudinal direction of the wire and elliptical in the direction parallel to the longitudinal direction of the wire.

[0033] (Characteristics of aluminum alloy wire) The aluminum alloy wire of the present embodiment is formed from an aluminum alloy having the above-mentioned chemical composition and metal structure. Specifically, the alloy wire has a tensile strength of 170 MPa or more at room temperature and an elongation of 10% or more. In addition, the wire has a strain rate of 10% at a temperature of 200°C. -5 The stress when deforming at a strain rate of 10 / sec is 60MPa or more. -5 The stress when it undergoes tensile deformation at 10000 / sec is 40 MPa or more. It also has a conductivity of 55% IACS or more.

[0034] From the viewpoint of flexibility, the wire diameter of the alloy wire is preferably 1 mm or less, and more preferably 0.3 mm to 1 mm.

[0035] <Method of manufacturing aluminum alloy wire> Next, a method for manufacturing the above-mentioned aluminum alloy wire will be described. The aluminum alloy wire of this embodiment can be manufactured by sequentially carrying out the steps of preparing a molten metal, casting, forming, drawing, and aging heat treatment. Each step will be described in detail below.

[0036] <Preparation process> First, a molten metal for forming an aluminum alloy wire is prepared. In this embodiment, an Al raw material, a Co raw material, a Zr raw material, and other alloy raw materials as necessary are mixed so that the molten metal has the above-mentioned chemical composition. Then, these raw materials are put into a melting furnace, for example, and melted by heating with a burner or the like. The method of mixing and melting the raw materials is not particularly limited, and can be performed by a conventionally known method. Here, a case where a Zr raw material and a Co raw material are added to an Al raw material will be described, but a Ni, Fe or Ti raw material may be added instead of the Co raw material.

[0037] The resulting molten metal is transferred to and stored in a storage tank (a so-called tundish), which is equipped with a pouring nozzle so that the molten metal can flow out of the storage tank.

[0038] <Casting process> Next, the molten metal is poured from the storage tank through a pouring nozzle into the mold. As the mold, for example, a continuous casting machine capable of belt wheel type continuous casting can be used. The continuous casting machine is configured to include, for example, a cylindrical wheel having a groove on its outer circumferential surface and a belt, and the belt is hung on a part of the outer circumferential surface of the wheel. With the continuous casting machine, the molten metal is poured into the space (groove portion) formed between the wheel and the belt, and solidified by cooling, thereby continuously forming a casting material.

[0039] In this embodiment, the temperature of the molten metal (casting temperature) is set to 800°C or 850°C. When the temperature of the molten metal (casting temperature) is 800°C, the molten metal is cooled relatively slowly in the mold. In contrast, when the temperature of the molten metal (casting temperature) is set to a high value of 850°C or higher, the molten metal is rapidly cooled in the mold. This suppresses the crystallization of Zr while crystallizing Co to form a cast material. This point will be described in detail below.

[0040] First, when the molten metal is rapidly cooled, it is possible to crystallize Co while suppressing the crystallization of Zr (Zr is kept in solid solution) as described below.

[0041] According to the study by the present inventors, when Zr forms a crystallized product with Fe in a cast material, the ductility of the cast material decreases, and the cast material may become difficult to draw. On the other hand, even if Co forms a crystallized product with Fe, it does not have much effect on the ductility of the cast material. For this reason, in the cast material, it is desirable to leave Zr in a solid solution without crystallizing it, while allowing Co to crystallize. However, when the molten metal is cooled, Zr also crystallizes together with Co, although in small amounts, so it is difficult to selectively keep only Zr in a solid solution.

[0042] In this regard, the inventors have focused on the fact that Co crystallizes (precipitates) more easily than Zr when the molten metal is cooled, that is, the crystallization rate (precipitation rate) of Co is faster than that of Zr. This difference in crystallization rate is due to the difference in diffusion rate in the aluminum solid phase.

[0043] Specifically, the diffusion rate of Co in the Al solid phase is equal to or greater than the self-diffusion rate of Al. Moreover, the solid solubility of Co in the Al phase in thermal equilibrium is very small, less than 0.05% at most. Therefore, Co easily aggregates and crystallizes in the Al structure even immediately after casting and solidifying from the molten metal. By crystallization, most of the Co crystallizes as a compound in the Al structure at the stage of the ingot (cast material) after casting. In addition to the crystallized compounds, solid-solubilized Co atoms also exist in the Al phase immediately after solidification. Immediately after solidification, supersaturated Co atoms, which are more than the solid solubility in thermal equilibrium, are solid-solubilized in the Al phase. However, by diffusing Co atoms at high speed in the Al phase, the supersaturated solid-solubilized Co atoms aggregate in a relatively short time to form a compound phase. As a result, by the time the cast material is cooled to room temperature after casting and solidification, most of the added Co atoms exist as a compound phase with Al, and the amount of Co atoms solid-solubilized in the Al phase remains small, less than 0.1%, which is close to the thermal equilibrium concentration.

[0044] On the other hand, the diffusion rate of Zr in the Al phase is significantly smaller than the self-diffusion rate of Al, and the precipitation rate in the Al structure is smaller than that of Co. Moreover, the maximum solid solubility of Zr in the Al phase in thermal equilibrium is about 0.3 to 0.4%, which is several times larger than that of Co. For this reason, Zr is difficult to crystallize at the stage of the cast material after casting, and most of it exists in a supersaturated solid solution state in the Al structure. In addition, since the diffusion of Zr is significantly slower than that of Co, the supersaturated solid solution state is maintained as it is even if the cast material after casting is stored at room temperature for a long time. The supersaturated solid solution state of Zr can be precipitated by heating at a temperature of 300°C or more by aging heat treatment.

[0045] From this, the inventors of the present invention considered that if the molten metal is solidified before Zr starts to crystallize, Zr can be kept in a solid solution state, and studied the cooling speed of the molten metal. As a result, it was found that the faster the cooling speed of the molten metal is increased, the more the Zr can be suppressed from crystallizing and the Zr can be maintained in a solid solution state in the resulting cast material, while the majority of Co is crystallized as an Al-Co-Fe compound. By dissolving Zr in a solid solution, the decrease in the ductility of the cast material due to the crystallization of Zr can be suppressed. That is, according to the cast material with less Zr crystallization, compared with the cast material with Zr crystallization, breakage can be suppressed even when the wire is drawn at a high processing degree, and an alloy wire with a small wire diameter can be produced.

[0046] Moreover, by setting the temperature of the molten metal to 850°C or higher, the solubility limit of Zr in Al can be increased. As a result, even if the Zr content is increased to, for example, 0.5 mass% to 1.0 mass%, Zr can be in a solid-solution state without crystallization. The upper limit of the temperature of the molten metal is not particularly limited as long as Zr can be solid-solved, but may be, for example, 900°C or lower, and preferably 870°C or lower.

[0047] The metal structure of the cast material obtained in the casting process is mainly composed of Al crystal grains surrounded by high-angle grain boundaries, and Co often crystallizes with Fe to form Al-Co-Fe compounds at the grain boundaries. Due to the formation of Al-Co-Fe compounds, there is little Fe in solid solution in the Al phase, which is a cause of reduced electrical conductivity, and there is also little precipitate (FeAl3), which is a cause of reduced elongation. Zr does not crystallize, but is in solid solution in the Al phase and grain boundaries.

[0048] In addition, the Al-Co-Fe compound does not reduce the ductility of the Al alloy like the FeAl3 compound, so it does not hinder the thinning of the alloy wire. The Al-Co-Fe compound is a compound containing at least Al, Co, and Fe, and may contain other metal elements. In addition, the Al-Co-Fe compound has an elongated shape in the ingot after casting.

[0049] In addition, in the casting process, the temperature of the molten metal flowing out from the pouring nozzle of the storage tank drops before being poured into the mold, and Zr, which is dissolved in Al, may start to crystallize. Therefore, from the viewpoint of suppressing the crystallization of Zr between the storage tank and the mold, it is preferable to heat the molten metal to be poured, and the temperature is preferably maintained at 800°C or higher, and more preferably maintained at 850°C or higher. This makes it possible to more reliably suppress the temperature drop during pouring of the molten metal, and improve the various properties of the alloy wire.

[0050] The method for heating the molten metal flowing out from the pouring nozzle is not particularly limited, but a known heating means, such as a burner, an electromagnetic heating device, a high-frequency heating device, etc., can be used between the pouring nozzle and the mold. It is preferable to provide such a heating means between the pouring nozzle and the mold so that the molten metal flowing down from the pouring nozzle can be heated.

[0051] In the casting process, from the viewpoint of solidifying the molten metal while keeping Zr in solid solution, the cooling rate is preferably 8°C / sec or more, more preferably 20°C / sec or more, for example, 40°C / sec. Although there is no particular upper limit, it is preferable to set it to 200°C / sec or less. From the viewpoint of more reliably achieving such a cooling rate, it is more preferable to use a Propertz type continuous casting machine rather than a twin roll type.

[0052] The cooling rate can be adjusted by appropriately changing the thickness of the mold. For example, by making the mold thicker, the ratio of the cross-sectional area of ​​the mold to the cross-sectional area of ​​the space in the mold (the cross-sectional area of ​​the cast material) can be increased, thereby improving the heat extraction efficiency. The cooling rate is expressed as the difference between the temperature of the molten metal when it is poured into the mold (e.g., 850°C) and the temperature at which the molten metal poured into the mold solidifies, divided by the time it takes for the molten metal to solidify after being poured into the mold.

[0053] <Forming process> Next, if necessary, the cast material is formed into a rod shape (so-called rough wire) so that it can be easily drawn. Here, the cast material is subjected to plastic processing so that the wire diameter becomes, for example, 5 mm to 50 mm. As the plastic processing, for example, a conventionally known method such as rolling, swaging, drawing, etc. may be used.

[0054] <Wire drawing process> Next, the rod-shaped cast material is subjected to cold wire drawing to be processed into a drawn wire material of a predetermined wire diameter. The wire drawing may be performed by a conventionally known method such as a drawing wire drawing using a die. The degree of processing is the ratio of the difference between the cross-sectional area of ​​the cast material and the cross-sectional area of ​​the drawn wire material to the cross-sectional area of ​​the cast material, and indicates the area reduction rate in the wire drawing process.

[0055] In the metal structure of the drawn wire material obtained in the wire drawing process, the Al crystal grains are elongated in the drawing direction by the wire drawing process, and processing strain is introduced. In addition, the Al-Co-Fe compounds that were crystallized in the cast material are finely crushed by the wire drawing process, and are finely and densely dispersed in the metal structure of the drawn wire material.

[0056] In this embodiment, the cast material has high ductility with the crystallization of Zr suppressed, so that the degree of wire drawing can be increased. From the viewpoint of crushing the Al-Co-Fe compound more finely and dispersing it more finely in the drawn wire material, it is preferable to wiredraw the cast material so that the cross-sectional area is 0.01 times or less, and the wire diameter of the drawn wire material is 2.0 mm or less. By setting the degree of wire drawing at such a level, it becomes easy to control the size of the Al-Co-Fe compound after the wire drawing to 20 nm to 1 μm. In addition, when Zr is precipitated in the aging heat treatment process described later, it becomes easy to control the size of the Al-Zr compound to 1 nm to 100 nm. Moreover, in the final alloy wire material, the precipitates can be precipitated more dispersedly.

[0057] In this embodiment, since the cast material has high ductility, it is possible to omit the annealing treatment (so-called intermediate annealing treatment) for mitigating the processing strain during wire drawing, which makes it possible to further suppress the coarsening of Al crystal grains due to recrystallization.

[0058] <Aging heat treatment process> Next, the drawn wire is subjected to an aging heat treatment to obtain the alloy wire of the present embodiment.

[0059] In the aging heat treatment, Zr, which is dissolved in the Al phase, is precipitated as an Al-Zr compound, and the processing strain introduced into the metal structure of the drawn wire material is alleviated. In this embodiment, by finely dispersing a Co compound in the drawn wire material, the recrystallization of Al is suppressed, and the processing strain can be alleviated by the recovery of Al crystals.

[0060] In this embodiment, the aging heat treatment is performed in two separate steps. In other words, the aging heat treatment includes two heat treatment steps (first heat treatment and second heat treatment). In the first heat treatment, the drawn wire material is heated at 200°C for 1 to 10 hours. In the second heat treatment performed thereafter, the drawn wire material is heated at 300°C to 350°C for 20 hours or more. These heat treatments are performed under atmospheric pressure. In addition, these heat treatments are performed in an inert atmosphere such as air or Ar gas. Here, the temperature of the drawn wire material is lowered to room temperature between the first heat treatment and the second heat treatment, but the first heat treatment and the second heat treatment may be performed consecutively without lowering the temperature of the drawn wire material to room temperature.

[0061] During the first heat treatment at 200°C, some of the processing strain disappears and subgrains are formed. Although the diffusion of dissolved Zr atoms is very slow, they gather through high-speed diffusion through the subgrains and form fine Al-Zr compounds even at this stage. It is also assumed that nucleation of Al-Zr compounds occurs in the matrix region within the subgrains due to the short-distance movement of Zr atoms. By carrying out the first heat treatment at a relatively low temperature, it is possible to form a large number of fine particles of Al-Zr compounds preliminary inside the Al alloy.

[0062] By setting the temperature of the subsequent second heat treatment to 300°C or higher, the subgrain boundaries formed in the first heat treatment stage can be grown, thereby increasing the ductility of the alloy wire. Moreover, since it becomes easier to precipitate Al-Zr compounds, the strength of the alloy wire can be increased while maintaining a low electrical conductivity. On the other hand, by setting the temperature to 350°C or lower, recrystallization can be suppressed and the subgrain boundaries can be maintained without disappearing, so that the strength of the alloy wire can be maintained high.

[0063] The time for heating the drawn wire in the second heat treatment (treatment time) is preferably 20 to 100 hours. By setting the time to 20 to 100 hours, the Al-Zr compound can be sufficiently precipitated while keeping the manufacturing cost low, and the electrical conductivity of the alloy wire can be reduced and the strength can be increased.

[0064] As described above, by performing the aging heat treatment in two stages, it is possible to disperse a larger amount of fine Al-Zr precipitate phases in the crystal grains of the alloy wire, as compared with the case where the first heat treatment is not performed in the aging heat treatment, for example, and thus it is possible to increase the strength of the alloy wire.

[0065] <Effects of the present embodiment> According to the present embodiment, one or more of the following advantages are obtained.

[0066] As a test for evaluating the properties of aluminum alloy wire, it is considered to measure the tensile strength of the aluminum alloy wire at room temperature. However, this evaluation method cannot detect the decrease in tensile strength caused by creep deformation that occurs in the aluminum alloy wire under high temperature conditions, and the reliability of the aluminum alloy wire cannot be ensured. In the aluminum alloy wire used for the connection terminal, stress relaxation occurs under high temperature conditions, and as a result, the electrical resistance of the aluminum alloy wire increases.

[0067] In contrast, the aluminum alloy wire of the present embodiment is a wire containing 0.3% to 0.6% by mass of Zr and 1.0% by mass or less of Co, Ni, Fe or Ti, and having a diameter of 0.1 mm or less. The aluminum alloy wire has a tensile strength of 170 MPa or more at room temperature and an elongation of 10% or more. In addition, the wire has a temperature of 200°C and a strain rate of 10 -5 The stress when deforming at a strain rate of 10 / sec is 60MPa or more. -5 The stress when it undergoes tensile deformation at 10000 / sec is 40 MPa or more. It also has a conductivity of 55% IACS or more.

[0068] Thus, the specified tensile strength is maintained even under high temperature conditions of 200°C or more and 250°C or more. High tensile strength under high temperature conditions indicates that stress relaxation is unlikely to occur in the alloy wire. Therefore, in the connection terminal part made of the aluminum alloy wire, it is possible to prevent the occurrence of loosening of the terminal. In other words, it is possible to prevent an increase in electrical resistance due to stress relaxation. The reason for obtaining such an effect is that the aluminum alloy wire has the above composition and the aging heat treatment is performed in two stages. Here, by performing the aging heat treatment in two stages, the fine Al-Zr precipitate phase stabilizes the subgrain structure formed during high-temperature deformation. This results in high creep deformation resistance. Therefore, the heat resistance of the aluminum alloy wire can be improved.

[0069] In addition, by setting the cooling rate of the molten copper high, it is possible to dissolve many additive elements, and to increase the tensile strength of the aluminum alloy wire. For example, when casting the molten metal, it is preferable to set the cooling rate to 20°C / sec or more. By quenching the molten metal under such conditions, it is possible to more reliably suppress the crystallization of Zr, while allowing Co to be more finely dispersed and crystallized. This makes it possible to obtain a higher level of balance of various properties.

[0070] In the above embodiment, the alloy wire using Co and Zr as alloy elements has been described, but the present invention is not limited to this, and Ni can be used instead of Co.

[0071] The alloy has a chemical composition consisting of 0.1-1.0 mass% Ni, 0.2-1.0 mass% Zr, 0.02-0.15 mass% Fe, 0.02-0.15 mass% Si, 0-0.2 mass% Mg, 0-0.10 mass% Ti, 0-0.03 mass% B, 0-1.00 mass% Cu, 0-0.50 mass% Ag, 0-0.50 mass% Au, 0-1.00 mass% Mn, 0-1.00 mass% Cr, 0-0.50 mass% Hf, 0-0.50 mass% V, 0-0.50 mass% Sc, and the balance: Al and unavoidable impurities.

[0072] In the manufacturing process (casting) of the alloy wire, most of Ni reacts with Al to form crystals (Al-Ni compounds), and exists as a compound phase in the finally obtained alloy wire. The Al-Ni compounds actually exist in the form of Al-Ni-Fe compounds that absorb Fe, which is inevitably present in the aluminum alloy. The Al-Ni-Fe compounds contribute to the refinement of Al recrystallized grains in the alloy and improve the elongation of the alloy wire. Ni may reduce the electrical conductivity of the alloy, but by setting the Ni content to 0.1 mass% to 1.0 mass%, it is possible to obtain the effect of having high levels of strength, elongation, and heat resistance due to Ni in a well-balanced manner while suppressing the decrease in electrical conductivity due to Ni in the alloy wire. The Ni content is preferably 0.2 mass% to 1.0 mass%, and more preferably 0.3 mass% to 0.8 mass%. When manufacturing an alloy wire using Ni, it is preferable to manufacture it in the same way as Co. In addition, the obtained alloy wire has the same metal structure as the alloy wire using Co, and has the above-mentioned characteristics.

[0073] (Example) Next, the present invention will be described in more detail based on examples and with reference to Table 1, however, the present invention is not limited to these examples.

[0074] [Table 1]

[0075] <Preparation of alloy wire> Example 1 In Example 1, 99.7% pure aluminum, Co, and Zr were blended so that Co, Zr, and Si had the composition shown in Table 1, and melted in an argon atmosphere using a high-frequency melting furnace. The temperature of the obtained molten metal was adjusted to 800°C, and then the molten metal was poured into a copper water-cooled mold (inner diameter: φ15 mm) and cast to obtain a cast material having a predetermined chemical composition. In this example, a burner was installed so that the molten metal to be poured could be heated, and the temperature of the molten metal to be poured was maintained at 800°C or higher. The cooling rate of the molten metal was 8°C / sec (seconds). The dimensions of the cast material were a cylinder with an outer diameter of φ15 mm and a length of 150 mm. This cast material was made into a rough wire of φ9.5 mm by swaging, and then repeatedly drawn by drawing through a die to thin it down to φ0.45 mm. No intermediate heat treatment was performed during the wire drawing through the die. The obtained wire having a diameter of 0.45 mm was subjected to a two-stage aging heat treatment to produce the alloy wire of Example 1. In this aging heat treatment, in the first heat treatment, the wire was held in a salt bath at 200°C for 5 hours, and then in the second heat treatment, the wire was held in a salt bath at 350°C for 24 hours.

[0076] Example 2 In Example 2, the amounts of Co and Zr added were changed so as to obtain the composition shown in Table 1, and an alloy wire was produced in the same manner as in Example 1, except that Ti was further added.

[0077] Example 3 In Example 3, an alloy wire was produced in the same manner as in Example 1, except that the amount of Zr added was changed to obtain the composition shown in Table 1, Ni and Ti were added instead of Co, the temperature of the molten metal during casting was set to 850°C, and the cooling rate was set to 40°C / sec.

[0078] Example 4 In Example 4, the amounts of Co and Zr added were changed to obtain the composition shown in Table 1, and an alloy wire was produced in the same manner as in Example 1, except that the temperature of the molten metal during casting was 850°C and the cooling rate was 40°C / sec.

[0079] (Comparative Examples 1 to 4) In Comparative Examples 1 to 4, alloy wires were produced in the same manner as in Examples 1 to 4, respectively, except that the aging heat treatment was carried out only once (the wire was held in a salt bath at 350° C. for 24 hours) instead of in two stages.

[0080] Comparative Example 5 In Comparative Example 5, an alloy wire was produced in the same manner as in Example 1, except that Co was not added and the amount of Zr added was changed.

[0081] Comparative Example 6 In Comparative Example 6, an alloy wire was produced in the same manner as in Comparative Example 9, except that the aging heat treatment was carried out only once (the wire was held in a salt bath at 350° C. for 24 hours) instead of in two stages.

[0082] (Evaluation method) The alloy wires thus produced were evaluated for tensile strength, elongation and electrical conductivity by the following methods.

[0083] <Tensile strength and elongation> The tensile strength and elongation of the alloy wire were measured by a tensile test of the alloy wire (test method conforming to JIS Z 2241 (test speed: 20 mm / min)). A Shimadzu 50N capacity load cell was used to measure the strength.

[0084] In this example, the tensile strength was measured at room temperature (25±5° C.), 200° C., and 250° C. The distance between the marks before the test was 100 mm, and the tensile strength at 200° C. and the tensile strength at 250° C. were measured at a strain rate of 10 -5The stress was measured during tensile deformation at 1000 / sec. When measuring at 200°C and 250°C, both ends of the test piece, a 0.45mm diameter wire, were fixed to a gripping jig and heated in a thermostatic chamber while adjusting the crosshead position of the testing machine so that a tension exceeding 0.5N was not applied to the test piece. After reaching the target temperature, the temperature was held for 2 hours or more to stabilize before the tensile test was performed. The test temperature was measured by attaching a thermocouple to the wire gripping jig.

[0085] In this example, a material was evaluated as having high strength if its room temperature tensile strength was 170 MPa or more, its tensile strength at 200° C. was 60 MPa or more, and its tensile strength at 250° C. was 40 MPa or more. Also, a material was evaluated as having high elongation if its room temperature elongation was 10% or more.

[0086] <Conductivity> The conductivity of the alloy wire was calculated by measuring the electrical resistance of the prepared alloy wire at 20° C. using a DC four-terminal method. In this example, a conductivity of 55% IACS or more was evaluated as having high conductivity.

[0087] <Evaluation Results> The various properties of the alloy wires of Examples 1 to 4 were measured, and as shown in Table 1, all of them had a room temperature tensile strength of 170 MPa or more, a tensile strength of 60 MPa or more at 200°C, a tensile strength of 40 MPa or more at 250°C, an elongation of 10% or more, and an electrical conductivity of 55% IACS or more, and were confirmed to be pass (◯).

[0088] On the other hand, as shown in Table 1, the alloy wires of Comparative Examples 1 to 6 did not satisfy all of these conditions.

[0089] When the differences in the evaluation results between the examples and the comparative examples were examined, it was confirmed that the differences in characteristics were due to the metal structure of the alloy wire.

[0090] Based on the above, by adding Co, Ti or Ni and Zr as alloying elements to molten aluminum, and then casting the alloy wire from the molten aluminum and subjecting it to a two-stage aging heat treatment, an aluminum alloy wire having a high level of strength, elongation, and electrical conductivity in a well-balanced manner can be obtained.

[0091] The invention made by the present inventors has been specifically described above based on an embodiment, but it goes without saying that the present invention is not limited to the above embodiment and can be modified in various ways without departing from the gist of the invention.

[0092] In addition, some of the contents described in the embodiment are described below. (Appendix 1) (a) A process of pouring molten aluminum into a mold to cast a casting material; (b) rolling the cast material to form a copper wire rod; (c) drawing the copper wire rod to form an aluminum alloy wire; (d) subjecting the aluminum alloy wire to a first heat treatment and then subjecting the aluminum alloy wire to a second heat treatment at a temperature higher than that of the first heat treatment; Including, The aluminum alloy wire is containing 0.2 to 1.0 mass% Zr and 0.1 to 1.0 mass% Co, with the balance being aluminum and unavoidable impurities, or containing 0.2 to 1.0 mass% Zr and 0.1 to 1.0 mass% Ni, with the balance being aluminum and unavoidable impurities; The tensile strength at room temperature is 170 MPa or more, The elongation is 10% or more, At a temperature of 250°C and a strain rate of 10 -5 The stress when deformed by tension at 1000 / sec is 40MPa or more. A method for manufacturing aluminum alloy wire.

[0093] (Appendix 2) In the method for producing an aluminum alloy wire according to (Appendix 1), In the step (a), the molten metal is cooled at a rate of 40° C. / sec or more to cast a casting material.

[0094] (Appendix 3) In the method for producing an aluminum alloy wire according to (Appendix 1 or 2), A method for producing an aluminum alloy wire, wherein in the step (d), a treatment time of the second heat treatment is longer than a treatment time of the first heat treatment.

Claims

1. A wire made of an aluminum alloy, The aluminum alloy contains 0.2 to 1.0 mass% Zr, 0.1 to 1.0 mass% Co, and the balance being aluminum and unavoidable impurities; The tensile strength at room temperature is 170 MPa or more, The elongation is 10% or more, At a temperature of 250°C and a strain rate of 10 -5 The stress when tensile deformed at 100 / sec is 40 MPa or more, Aluminum alloy wire.

2. A wire made of an aluminum alloy, The aluminum alloy contains 0.2 to 1.0 mass% Zr, 0.1 to 1.0 mass% Ni, and the remainder is aluminum and unavoidable impurities; The tensile strength at room temperature is 170 MPa or more, The elongation is 10% or more, At a temperature of 250°C and a strain rate of 10 -5 The stress when tensile deformed at 100 / sec is 40 MPa or more, Aluminum alloy wire.

3. The aluminum alloy wire according to claim 1 or 2, The aluminum alloy wire further contains 0 to 0.10 mass % of Ti.

4. The aluminum alloy wire according to any one of claims 1 to 3, An aluminum alloy wire having a room temperature electrical conductivity of 55% IACS or more.

Citation Information

Patent Citations

  • JP1972002903U

  • Preparation of heat resistant aluminum alloy conductor

    JP1982039164A

  • Manufacture of high-strength heat-resistant aluminum alloy with electric conductivity

    JP1983147546A

  • Electroconductive, heat-resistant aluminum alloy wire and production method therefor

    JP2002302727A

  • Aluminum alloy wire and method for producing the same

    JP2019196519A